The colloidal gold nanoparticle‐based lateral flow immunoassay for fast and simple detection of plant‐derived doping agent, higenamine. Issue 4 (25th November 2020) - Nuntawong, Poomraphie; Ochi, Akihiro; Chaingam, Jiranan; Tanaka, Hiroyuki; Sakamoto, Seiichi; Morimoto, Satoshi
Abstract: Higenamine (HM), an alkaloid found in various plant species, is obtained when norcoclaurine synthase selectively condenses dopamine and 4‐hydroxyphenylacetaldehyde to give ( S )‐higenamine (( S )‐HM). The World Anti‐doping Agency has listed HM as a prohibited agent in athletics. As a result, many commercial, academic, and regulatory bodies across the globe are invested in finding a rapid method for ( S )‐HM detection. In the current study, a lateral flow immunoassay (LFA) was developed in which the relevant biosensor was generated as a conjugate of the monoclonal antibody against ( S )‐HM (namely, MAb E8) and colloidal gold nanoparticles. The HM–γ‐globulin conjugates and rabbit anti‐mouse IgG antibodies were placed in the test and control zones, respectively. The free ( S )‐HM molecules in the samples and the immobilized HM–γ‐globulin conjugates competitively reacted with the developed biosensor in the LFA. An inverse relationship existed between the biosensors' visible response, which was noted by the variation in the intensity of a pinkish spot in the test zone, and the content of the free ( S )‐HM. The limit of detection of the developed LFA was 156 ng/mL. Various validation methods confirmed that the LFA exhibited sufficient sensitivity, selectivity, repeatability, and reliability, making it ideal for ( S )‐HM detection in plant samples and plant‐containing products. The developed system required only a small sample volume (20 μL) and a concise sample preparation time compared with conventional LFAs. Thus, the LFA reported in this study could serve as a rapid response kit for the detection of ( S )‐HM in plant samples. Abstract : Higenamine (HM) is an alkaloid doping agent that can be isolated from various kinds of plant. A lateral flow immunoassay (LFA) was developed in which the relevant biosensor was generated as a conjugate of the monoclonal antibody against ( S )‐HM and colloidal gold nanoparticles. Validation methods confirmed that the LFA exhibited sensitivity, selectivity, and repeatability. The LFA could serve as a rapid response kit for the detection of ( S )‐HM in plant samples.